Double-site recognition of pathogenic bacterial whole cells based on an antibiotic-affinity strategy1. Issue 62 (11th August 2015) - Gao, Hongfei; Yang, Shijia; Han, Jing; Xiong, Jie; Kong, Weijun; Li, Chong; Liao, Guojian; Fu, Zhifeng
<x xml:space="preserve">Abstract</x> An antibiotic-affinity strategy was designed for direct assaying whole cells of a pathogenic bacterium based on the strong affinity of the antibiotic agent to bind to the cell wall of the bacterium.